2021
DOI: 10.1155/2021/5594370
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Angiogenic Effect of Chitosan/Graphene Oxide Hydrogel Scaffolds on EPCs

Abstract: Angiogenesis in the field of tissue engineering has attracted significant attention. Graphene oxide has become a promising nanomaterial in tissue engineering for its unique biochemical properties. Therefore, herein, a series of chitosan (CS)/graphene oxide (GO) hydrogel scaffolds were synthesized by crosslinking CS and GO at different concentrations (0.1, 0.5, and 1.0 wt.%) using genipin. Compared with the CS hydrogel scaffolds, the CS/GO hydrogel scaffolds have a better network structure and mechanical streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…These composites exhibit performance which overcomes limitations observed by the individual components (i.e., poor mechanical performance and low biocompatibility, respectively). Recent studies have shown that the synergistic effect between CS and GO generates hybrids with not only improved thermal stability, mechanical and optical properties ( Chen et al., 2019 ; Cobos et al., 2017 ; Kumar and Koh, 2014 ; Zhang et al., 2018a ) but also excellent in vitro and in vivo biocompatibility ( López Tenorio et al., 2019 ; Valencia et al., 2021 ; Zhang et al., 2021 ), angiogenic and cell growth effect ( Zhang et al., 2018b , 2021 ), antimicrobial properties ( Grande et al., 2017 ; Khalil et al., 2020 ), electrical conductivity ( Jiang et al., 2019 ) and adsorption capacities ( Wu et al., 2020a ; Yu et al., 2017b ), etc. Therefore, nanocomposites containing CS and GO have been widely created for developing improved thermomechanical and antimicrobial properties of food packaging film ( Ahmed et al., 2017 ; Grande et al., 2017 ), conductive three-dimensional scaffolds, coating, and nanofiber for tissue engineering ( Arnaldi et al., 2020 ; Cao et al., 2017 ; Jiang et al., 2019 ; Karimi et al., 2019 ), nanoparticle and hydrogel with great loading capacity and releasing profile for drug delivery ( Wang et al., 2018a ; Zhao et al., 2017b ), antibacterial film and hydrogel patch for wound healing ( Najafabadi et al., 2020 ; Yang et al., 2019c ), nanofiber and film with high load carrying capacity and electrochemical properties for biosensor ( Fazial and Tan, 2021 ; Li et al., 2019 ), sponge and membrane with strong adsorption power for wastewater treatment ( Bandara et al., 2019 ; Qi et al., 2018 ), and so on .…”
Section: Introductionmentioning
confidence: 99%
“…These composites exhibit performance which overcomes limitations observed by the individual components (i.e., poor mechanical performance and low biocompatibility, respectively). Recent studies have shown that the synergistic effect between CS and GO generates hybrids with not only improved thermal stability, mechanical and optical properties ( Chen et al., 2019 ; Cobos et al., 2017 ; Kumar and Koh, 2014 ; Zhang et al., 2018a ) but also excellent in vitro and in vivo biocompatibility ( López Tenorio et al., 2019 ; Valencia et al., 2021 ; Zhang et al., 2021 ), angiogenic and cell growth effect ( Zhang et al., 2018b , 2021 ), antimicrobial properties ( Grande et al., 2017 ; Khalil et al., 2020 ), electrical conductivity ( Jiang et al., 2019 ) and adsorption capacities ( Wu et al., 2020a ; Yu et al., 2017b ), etc. Therefore, nanocomposites containing CS and GO have been widely created for developing improved thermomechanical and antimicrobial properties of food packaging film ( Ahmed et al., 2017 ; Grande et al., 2017 ), conductive three-dimensional scaffolds, coating, and nanofiber for tissue engineering ( Arnaldi et al., 2020 ; Cao et al., 2017 ; Jiang et al., 2019 ; Karimi et al., 2019 ), nanoparticle and hydrogel with great loading capacity and releasing profile for drug delivery ( Wang et al., 2018a ; Zhao et al., 2017b ), antibacterial film and hydrogel patch for wound healing ( Najafabadi et al., 2020 ; Yang et al., 2019c ), nanofiber and film with high load carrying capacity and electrochemical properties for biosensor ( Fazial and Tan, 2021 ; Li et al., 2019 ), sponge and membrane with strong adsorption power for wastewater treatment ( Bandara et al., 2019 ; Qi et al., 2018 ), and so on .…”
Section: Introductionmentioning
confidence: 99%
“…[180,181,366] Multilayered, tubular structures have been typically made by either stacking multiple films or nanofiber mats that are then rolled together [337] or electrospinning layers directly onto a cylinder. [365,366] Qian et al created layered, tubular scaffolds in which the innermost layer consisted of polydopamine and arginylglycylaspartic acid (RGD), followed by two layers of a PCL/graphene film, and an outermost layer of polydopamine and RGD. [365] Polydopamine and RGD layers facilitated cell adhesion while PCL/graphene layers enabled local electrical activity.…”
Section: Porous 3d and Tubular Scaffoldsmentioning
confidence: 99%
“…Compared to 2D substrates, scaffolds with 3D geometries can better recapitulate the microenvironment surrounding a cell in CNS tissues. Conductive 3D scaffolds have been made using techniques that include layer-by-layer assembly, [364][365][366] often combined with electrospinning as with the conduits described above, [364,365] and 3D printing. [367][368][369] Stacking and annealing 2D, conductive layers have led to the production of relatively thick, 3D cell scaffolds.…”
Section: Porous 3d and Tubular Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations